2013
DOI: 10.1037/a0034443
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in associative memory for emotional and nonemotional integrative representations.

Abstract: Events often include novel combinations of items. Sometimes, through the process of integration, we experience and remember these items as parts of a whole rather than as separate entities. Recent research with younger adults has demonstrated that successfully integrating two non-emotional items at encoding, instead of imagining them separately, produces a disproportionately larger associative memory benefit than integrating an emotional and a non-emotional item (Murray & Kensinger, 2012). In the first study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Indeed, brain imaging indicates that the hippocampal structures that discriminate reward are also involved in binding associations in memory ( Wolosin, Zeithamova, & Preston, 2012 , 2013 ). Similarly, there is evidence that positive emotion can enhance integrative associative memory ( Murray & Kensinger, 2013 , 2014 ). Thus, both reward and emotion are candidate “drivers” for the binding effects we observe in relation to the self.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, brain imaging indicates that the hippocampal structures that discriminate reward are also involved in binding associations in memory ( Wolosin, Zeithamova, & Preston, 2012 , 2013 ). Similarly, there is evidence that positive emotion can enhance integrative associative memory ( Murray & Kensinger, 2013 , 2014 ). Thus, both reward and emotion are candidate “drivers” for the binding effects we observe in relation to the self.…”
Section: Discussionmentioning
confidence: 98%
“…Murray and Kensinger (2013) found that an encoding task that encouraged participants to form a single image that integrated two words in a pair enhanced older adults’ associative memory for positive and negative word pairs but not non-emotional word pairs. For younger adults, on the other hand, the picture integration task enhanced the cued recall of non-emotional words more than emotional words.…”
Section: Age Differences In Associative Memorymentioning
confidence: 94%
“…Older adults also produce vividness ratings that are as high as young adults when they imagine familiar places (Robin & Moscovitch, 2017). Critically, older adults report subjective vividness levels that are as high as young adults when they fill-in mental imagery questionnaires Murray & Kensinger, 2013;Pierce & Storandt, 1987;Uittenhove et al, 2015). However, whether these judgements reflect the richness of the content of what older participants have in mind has been questioned (Pierce & Storandt, 1987), but not examined yet.…”
Section: Jeunehomme Et Al 2020)mentioning
confidence: 99%